IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI) 2014
DOI: 10.1109/bhi.2014.6864295
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of trustworthy health videos from YouTube

Abstract: Health information retrieval and YouTube can be used as powerful tools aimed to improve users' health knowledge. However, YouTube videos must be carefully analysed in order to avoid misleading health content, such as inaccurate health information, non-up-to-date treatments, false medical products promoted by for-profit organizations, and information not related to health. This paper presents an approach for retrieving trustworthy health videos from YouTube. Our algorithm automatically identifies videos coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…A standard moderating service for educational videos would potentially improve video quality, although this would be logistically challenging and costly to implement, given the volume of new content added to the system daily. 20 Domainbased ranking, a system that returns videos coming from trusted sources (hospitals and health organisations) higher up in the search results, might be one method of improving the identifi cation of trustworthy health-related videos on YouTube, 23 although in our study only one video was found to have come from a recognised medical educational institution. Additionally, this group has previously suggested that organisations with a role in the education of medical students and other healthcare professionals should make an active effort to identify good-quality online teaching resources, perhaps through use of some form of 'kitemark' that need not be restricted to the YouTube website.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A standard moderating service for educational videos would potentially improve video quality, although this would be logistically challenging and costly to implement, given the volume of new content added to the system daily. 20 Domainbased ranking, a system that returns videos coming from trusted sources (hospitals and health organisations) higher up in the search results, might be one method of improving the identifi cation of trustworthy health-related videos on YouTube, 23 although in our study only one video was found to have come from a recognised medical educational institution. Additionally, this group has previously suggested that organisations with a role in the education of medical students and other healthcare professionals should make an active effort to identify good-quality online teaching resources, perhaps through use of some form of 'kitemark' that need not be restricted to the YouTube website.…”
Section: Discussionmentioning
confidence: 54%
“…However, previous work carried out by this group on the quality of medical education material on YouTube revealed a signifi cant body of poor-quality and, in some cases, factually incorrect resources. 16 Other groups looking at both medical education material 21,22 and patient information 23 have also expressed concerns regarding misleading information on the website. The benefi ts of high-quality information on YouTube are severalfold because it can be used for private study or integrated into classroom teaching, while being engaging and appealing to multiple learning styles simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…[27] The issue of credibility and trustworthy issues of YouTube videos forced Kreslen et al to recommend a novel method of re-ranking health related YouTube videos according to certain domains and according to source of the video uploader. [36] The findings of this study indicated that the most common content of AD videos was signs and symptoms. On the contrary, the AD informal caregiver education on YouTube is generally lacking.…”
Section: Discussionmentioning
confidence: 69%
“…[ 15 ] YouTube videos must be carefully analyzed in order to avoid misleading, inaccurate, obsolete, and incorrect health content, which could be improvised using domain-based ranking. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%